WILLINGNESS TO PAY BERAS MERAH ORGANIK “BERASKITA” DI PERUM BULOG SUB DIVRE MADIUN - Preliana Dewi, Primatora Citra Eka; Relawati, Rahayu; Mufriantie, Fithri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Organic red rice has many health benefits compared to white rice. Organic rice includes special rice that is not subject to the Highest Retail Price (HET) regulation set by the government, so this rice does not have a maximum price limit.The purpose of this study is to describe consumer market segmentation, analyze the value of consumers’ Willingness to Pay and analyze the factors that influence consumers’ Willingness to Pay. Organic red rice has many health benefits compared to white rice. Organic rice includes special rice that is not subject to the HET (Highest Retail Price) regulation set by the government, so this rice does not have a maximum price limit. The data analysis used is descriptive analysis, Contingent Valuation Method (CVM) analysis and Mutiple Linear Regression analysis. The research was conducted at Perum Bulog Sub Divre Madiun. The sampling method used was the accidental sampling method. The results showed that consumer market segmentation has an influence on determining the value of consumer Willingness to Pay. The Willingness to Pay value for organic red rice “BerasKita” is Rp 23.825, which is higher than the current price. Factors that have a significant effect on Willingness to Pay are attribute of organic red rice. Improvement recommendations should be able to maintain and improve product quality.